MiR-708 regulates the biological behavior of childhood leukemia cells by binding to the 3'utr end of the target gene and reducing the level of the target gene: Regulation of leukemia cells biological behavior by miR-708 - Li, Yan; Zhang, Ying; Guan, Lei (Cellular and Molecular Biology, 2023)
This study was performed to analyze the biological behavior of childhood leukemia cells regulated by miR-708 by binding to the 3' UTR end of the target gene and reducing the level of the target gene. In this regard, human leukemia Jurkat cell lines were selected and divided into a control group, miR-708 overexpression group and miR-708 inhibition group. MTT assay was used to detect the cell proliferation inhibition rate, flow cytometry was used to detect the apoptosis rate and cell cycle change, the scratch test was used to detect the cell migration capacity, and Western Blot assay was used to detect the expression of CNTFR, apoptosis and JAK/STAT pathway related proteins. To verify the binding site of miR-708 and target gene CNTFR. The results showed that the cell proliferation inhibition rate, apoptosis rate, G1 phase ratio, Bax protein, and CNTFR protein in the miR-708 overexpression group were significantly lower than those in the control group at each time point, while the S phase ratio, Bcl-2 protein, cell migration ability, JAK3 and STAT3 protein were significantly higher than those in the control group (P<0.05). The results of the miR-708 inhibition group were contrary to those of the miR-708 overexpression group. The binding sites of miR-708 and CNTFR were predicted by TargetScan bioinformatics software. It was found that there were two binding sites of miR-708 and CNTFR, 394-400 bp and 497-503 bp respectively. In conclusion, miR-708 can reduce the expression of CNTFR by binding to the target gene CNTFR3' UTR, activate the JAK/STAT pathway to regulate apoptosis-related proteins, reduce apoptosis, and enhance the migration ability of leukemia cells.